Analisis Tingkat Penjualan Tiket.Com Online Dalam Meningkatkan Profitabilitas Perusahaan Pt Satu Kosong Tujuh - sopiani, sopiani (CV. Kalimasada Group, 2023)
The main problem in this research is analysis of the level of online Tiket.com Sales in Increasing the Profitability of the Company PT. Satu Blank Seven This study aims to explain the Level of Sales of Tiket.com Online in Increasing the Profitability of the Company PT. Satu Blank Seven in increasing customer satisfaction at PT. Satu Kosong Tujuh Tangerang. The research method that the author uses is a non-statistical quantitative type. With the approach method or data collection technique that the authors use is through observation, interviews, and documentation. Data processing is done by means of data reduction, data presentation and drawing conclusions, then described and described. The results of this study address the Analysis of Online Tiket.com Sales Levels in Increasing Company Profitability PT. Satu Kosong Tujuh is able to inspire and influence employees, with this leadership style making employees trust, loyal and respect for their leaders, and motivated more than expected. And the Tiket.com Sales Level applied by the leadership of PT. Satu Kosong Tujuh, namely placing humans as the main and most important factor in the organization.